Romantic partners and young adult offending: considering the role of partner's socioeconomic characteristics - Widdowson, Alex O. (Criminology, 2021)
In this study, we examined whether and to what extent the effects on offending of marriage and different types of cohabitating partnerships depend on the romantic partner's socioeconomic status (SES). Such research addresses a key gap in knowledge regarding potential heterogeneity of effects on behavior of romantic partnerships. Drawing on the National Longitudinal Survey of Youth 1997, we examined the within-individual effects of three romantic partner's socioeconomic characteristics-education, employment, and income-on offending from ages 18 to 34. Results revealed that marriage was related to reductions in arrest only for those whose spouse was employed (full or part time) and had income. In contrast to marriage, partner SES was not related to arrest among those who cohabited with a partner they never married. Additionally, partner SES was often associated with reductions in arrest among those who cohabited with a partner they later married, but the reductions were statistically indistinguishable across levels of partner SES. Lastly, these effects were experienced similarly for low- and high-SES individuals alike, and no gender differences were detected in these effects. Our findings suggest that important life events such as marriage and cohabitation can be behavior-altering transitions, but the effects of these events are variable.